Comparing the Efficacy of Leishman–Giemsa Cocktail Stain, Giemsa Stain, and Papanicolaou Stain in Potentially Malignant Oral Lesions: A Study on 540 Cytological Samples - Sidhu, Supreet K. (J Cytol, 2018)
BACKGROUND: This study was planned to compare and evaluate the staining efficacy of Leishman–Giemsa cocktail (LG), Papanicolaou, and Giemsa stain (G) in potentially malignant disorders and malignant lesions. AIMS: To evaluate the quality of nuclear and cytoplasmic staining of LG with G, and rapid Papanicolaou stain (Pap) and to compare the total staining efficiency of LG against G and P. MATERIALS AND METHODS: One hundred and eighty participants were studied under three groups – 60 as healthy controls, 60 with potentially malignant disorders, and 60 with malignant lesions; smears were taken thrice from the buccal mucosa. One smear was fixed with Bio-Fix spray and other two smears were allowed to air dry for 2–3 minutes. Then, the ethyl alcohol-fixed smear was stained with Pap and the two other air-dried smears were stained with G and LG stains. Analysis was done using Friedman test and Wilcoxon Signed Rank Test with SPSS Version 15.0. RESULTS: In the normal group, staining of LG was highly significant (P < 0.001). Among potentially malignant lesions, LG was observed to be highly significant (P < 0.001) when compared with G and was not significant when compared with Pap (P = 0.186). In the malignant group, LG was highly significant (P < 0.001). LG was superior with the highest average staining score of (2.018) than Pap and G. CONCLUSION: LG cocktail is a better stain with excellent cytoplasmic and nuclear staining intensity compared to Pap and G stains.